Анализа уретка серума за нивое Hcy, HMGB1 и TLR4 и поларизацију мононуклеарних макрофага код акутног церебралног инфаркта: Нивои серума Hcy, HMGB1 и TLR4 и поляризација мононуклеарних макрофага код АЦИ - Chen, Yinxin; Tan, Taotao (Journal of Medical Biochemistry, 2025)
[Objective] To explore the correlations between homocysteine (Hcy), high mobility group protein B1 (HMGB1), and Toll-like receptor 4 (TLR4) levels and the polarization of mononuclear macrophages among individuals who were admitted with acute cerebral infarction (ACI). [Methods] The case group was made up of 214 ACI patients who were admitted to the hospital between August 2022 and August 2024, whereas the control group was made up of 100 healthy people who had physicals over the same time frame. A comparison was made between the two groups’ admission serum Hcy, HMGB1, and TLR4 levels. The polarization conditions of the mononuclear macrophages in the two groups were compared [proportion of M1-type cells, proportion of M2-type cells, M1/M2 ratio, M1-type polarization markers (interleukin-1β, tumor necrosis factor-α), and M2-type polarization markers (interleukin-10, transforming growth factor-β)]. to investigate the connections between the polarization of mononuclear macrophages and the levels of Hcy, HMGB1, and TLR4 in ACI patients, as well as the associations between these levels and the prognosis of ACI patients. Serum levels of Hcy, HMGB1, and TLR4 were compared between the ACI patients who were split into groups with excellent and poor prognoses. The prognostic efficacy of Hcy, HMGB1, and TLR4 for the prognosis of ACI patients was evaluated using receiver operating characteristic (ROC) curves. [Results] Serum Hcy, HMGB1, and TLR4 levels in the case group were considerably higher (P<0.05) than those in the control group. Interleukin-1β and tumor necrosis factor-α levels, the M1/M2 ratio, and the percentage of M1-type cells were all considerably greater (P<0.05) in the case group compared to the control group, although transforming growth factor-β and interleukin-10 levels were significantly lower (P<0.05). Serum Hcy, HMGB1, and TLR4 levels in ACI patients were found to be negatively correlated with interleukin-10 and transforming growth factor-β (P<0.05) and positively correlated with the proportion of M1-type cells, the M1/M2 ratio, and the levels of interleukin-1β and tumor necrosis factor-α (P<0.05), according to the results of the Pearson correlation analysis. Serum Hcy, HMGB1, and TLR4 levels were substantially higher (P<0.05) in the poor prognosis group than in the good prognosis group. With area under the curve (AUC) values of 80.00%, 77.80%, and 0.840 for sensitivity, specificity, and AUC, respectively. The ROC curve analysis showed that the combined prediction of Hcy, HMGB1, and TLR4 levels had a comparatively high efficacy in predicting the prognosis of ACI patients. [Conclusion] Patients with ACI had elevated levels of Hcy, HMGB1, and TLR4 expression in their peripheral blood. These levels are anticipated to be biomarkers for the clinical diagnosis and treatment of ACI and are strongly correlated with the polarization of mononuclear macrophages and patient prognosis.